An electrocortical investigation of voluntary emotion regulation in combat-related posttraumatic stress disorder. (30th March 2016) - Fitzgerald, Jacklynn M.; MacNamara, Annmarie; DiGangi, Julia A.; Kennedy, Amy E.; Rabinak, Christine A.; Patwell, Ryan; Greenstein, Justin E.; Proescher, Eric; Rauch, Sheila A.M.; Hajcak, Greg; Phan, K. Luan
Abstract: Posttraumatic stress disorder (PTSD) – a debilitating disorder characterized by severe deficits in emotion regulation – is prevalent among U.S. military veterans. Research into the pathophysiology of PTSD has focused primarily on emotional reactivity, showing evidence of heightened neural response during negative affect provocation. By comparison, studies of brain functioning during the voluntary regulation of negative affect are limited. In the current study, combat-exposed U.S. military veterans with ( n =25) and without ( n =25) PTSD performed an emotion regulation task during electroencephalographic (EEG) recording. The late positive potential (LPP) was used as a measure of sustained attention toward, and processing of, negative and neutral pictures, and was scored prior to and after instructions to either maintain or down-regulate emotional response using the strategy of cognitive reappraisal. Results showed that groups did not differ in picture-elicited LPP amplitude either prior to or during cognitive reappraisal; reappraisal reduced the LPP in both groups over time. Time-dependent increases in LPP amplitude as a function of emotional reactivity maintenance were evident in the non-PTSD group only. This latter finding may signal PTSD-related deficits in sustained engagement with emotion-processing over the course of several seconds. Highlights: We test veterans with and without PTSD on voluntary regulation ability. Veterans with PTSD do not show deficits in regulation, as measured via ERPs. Veterans without PTSD show increases in ERP amplitude during sustained emotion. Findings may signal PTSD-related deficits in sustained emotion processing.